PENGARUH GAJI DAN STATUS KARYAWAN TERHADAP LOYALITAS KARYAWAN PADA PT CITRA BUANA BATAM INDUSTRI - Joiwi, Joiwi; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2021)
The purpose of this study is to know partially and simultaneously between salary and employee status towards employee loyalty.The technique used in this study is to identify partial effects (test t) and simultaneous (test f) between salary variables (X1) and employee status (X2) on employee loyalty (Y) in PT Citra Buana Batam Industri. The method use in this study are descriptive analysis and use data analysis SPSS software program version 26 . Data technique is done by using questionnaires distribution to the monthly employees of PT Citra Buana Batam Industri as many as 114 respondent. The results of the coefficient determinations (R2) in the summary model viewed by the R Square salary variable, employee status and employee loyalty be 0.184 or 18.4%, while the test t on the salary variables with a significant 0.001<0.05 and employee status variables with a significant 0,000< 0.05 each variable has a significant effect on employee loyalty. the results of the test F amounted to 12,501>2,69 and the significance of 0,000<0,05 which indicates variable salary and employee status simultaneous significant effect towards employee loyalty. Keywords: Salary; Employee Status; Employee Loyalty.